World beyond borders : an introduction to the history of international organizations - MacKenzie, David Clark, 1953- ([Toronto] : University of Toronto Press, 2010)
"This short and well-written overview provides essential information on the history of international organizations (IOs), with particular focus on the League of Nations, the development of the United Nations, and the UN system. Starting at the beginning of the twentieth century, when there were very few international organizations in existence, A World Beyond Borders traces the growth of IOs through to the close of the century, when there were literally thousands at the heart of the international system.
Following this chronological order, the book examines how international organizations became the major legal, moral, and cultural forces that they are today, involved in all aspects of international relations including peacekeeping, disarmament, peace resolution, human rights, diplomacy, and environmentalism."--Pub. desc.
An introduction to international organizations -- The League of Nations -- Wartime internationalism and international organizations -- The UN in the Cold War years -- Regional and other international organizations -- The world of international NGOs -- The UN in the modern era -- Appendices: The Covenant of the League of Nations -- The Charter of the United Nations -- The Universal Declaration of Human Rights.
Includes bibliographical references (pages 185-196) and index.
Also issued in electronic formats.
Keywords: United Nations -- History; United Nations; Nations Unies -- Histoire; Nations Unies -- Histoire; International agencies -- History; International agencies; Internationale Organisation; Organisations internationales -- Histoire; Organisations internationales -- Histoire; History